“Justice Beyond The Principal Offender: A Critical Analysis Of Accomplice Liability In Criminal Cases” - Sharma , Aishwarya (Trinity Law Review, 2023)
Accomplices play a vital role in criminal activity, providing assistance to the  principal offender before, during, or after the commission of crime. Their actions  can range from providing transportation or weapons to acting as a lookout or  getaway driver. Accomplices may also help the principal to conceal evidence or  avoid capture, or simple encourage or persuade them to commit the crime in the  first place.
Keywords: Justice; Accomplice; Criminal Cases